Multi-criteria decision making for identification of unbalanced bidding - Su, Limin; Wang, Tianze; Li, Huimin; Chao, Yongchao; Wang, Lunyan (Journal of Civil Engineering and Management, 2020)
Unbalanced bidding is a serious problem in the competitive bidding practices of construction projects. Identification and prevention of unbalanced bidding is an important and complexity task for owners. This paper aims to propose an identification model of unbalanced bidding from multi-criteria decision making (MCDM) perspective. The VIKOR method is employed to detect unbalanced bidding, in which the line items and bidders are considered as criteria and alternatives in MCDM, respectively. And the engineer’s estimated price is chosen as evaluation benchmarking. Then relative distances between engineer’s estimated price and each bidding unit price are calculated to build decision matrix. The weights of factors are determined using entropy weight method. To illustrate the effectiveness of the proposed model, an application example is tested in detecting unbalanced bidding. Finally, the sensitivity analysis about VIKOR method is given. It shows that the presented model would provide a robust decision making support for owner in identifying unbalanced bidding.First published online 18 December 2019